Ester Boserup's Legacy on Sustainability Orientations for Contemporary Research - Fischer-Kowalski, Marina; Reenberg, Anette; Schaffartzik, Anke; Mayer, Andreas (Human-Environment Interactions, 2014)
Arising from a scientific conference marking the 100th anniversary of her birth, this book honors the life and work of the social scientist and diplomat Ester Boserup, who blazed new trails in her interdisciplinary approach to development and sustainability.